Eksekusi putusan hakim dalam sengketa perdata di Pengadilan Negeri Sleman - Hartini, Sri; Widihastuti, Setiati; Nurhayati, Iffah (Jurnal Civics: Media Kajian Kewarganegaraan, 2017)
This article is based on research intended at describing the execution of verdict of private case in court of Sleman Regency and its obstacles. It was a descriptive qualitative research. It was found that the excecution of verdict of private case in court of Sleman Regency begins by accustion or submission of execution by appelant and ends execution by confiscation. Its obstacle were: (1) its high cost as burdance of appelant; (2) the lack of qualified personels; and (3) the rivalry or rejection of accusted. The efforts to overcome these obstacles were: (1) the chief of regency court encourages both sides to compromise between initiator of accustion and his/her rival (accusted) peacefully; (2) send a personel substitude of seizure in calling conflicting side and proposing aditional personels but not yet succesful; and (3) the persoel of seizure inform or sends the unsolved problem through electrinic devices to Sleman Regency in order to suspend its execution.